Español Español - Loaiza, Santiago; Posada Hernandez, Julián Alberto (Revista Ecos de la Academia, 2021)
This research aims to analyze the relationship and interaction of supply and demand, of the professional services that are published in Facebook groups, aimed at graphic designers and visual communicators in Ecuador. The methodology used was based on qualitative ethnographic protocols, through observation and insertion in virtual communities. Key piece was the analysis of content dimensions and type of offer. The results obtained show that the labor market is inclined towards the search for independent professionals who can and know how to work by project or product in a given time. One of the conclusions that stand out in the study is that the graphic design sector must adapt more and more towards a new environment where unconventional professional relationships predominate, placing emphasis on the portfolio of services and consolidating as integral advisors in visual communication.
Keywords: Español